2021
DOI: 10.14569/ijacsa.2021.0121176
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Commerce Product Recommendation using Enhanced Conjoint Analysis

Abstract: While finding any product, there are many identical products sold in the marketplace, so buyers usually compare the items according to the desired preferences, for example, price, seller reputation, product reviews, and shipping cost. From each preference, buyers count subjectively to make a final decision on which product is should be bought. With hundreds of thousands of products to be compared, the buyer may not get the product that meets his preferences. To that end, we proposed the Enhanced Conjoint Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The main processes of preprocessing include removing irrelevant words, handling duplicates to ensure data integrity, normalizing data to a consistent format, handling outliers to prevent skewed analysis, and performing feature extraction to reveal underlying patterns in the dataset [20] [21] [22]. By performing these preprocessing steps, researchers create a cleaner, more standardized dataset that becomes the basis for accurate and in-depth data analysis.…”
Section: B Processing Data 1) Preprocessingmentioning
confidence: 99%
“…The main processes of preprocessing include removing irrelevant words, handling duplicates to ensure data integrity, normalizing data to a consistent format, handling outliers to prevent skewed analysis, and performing feature extraction to reveal underlying patterns in the dataset [20] [21] [22]. By performing these preprocessing steps, researchers create a cleaner, more standardized dataset that becomes the basis for accurate and in-depth data analysis.…”
Section: B Processing Data 1) Preprocessingmentioning
confidence: 99%
“…This preprocessing process involves cleaning and preparing the data for further analysis. This includes removing special characters, addressing missing or duplicate data, and converting the tweet text into a format that can be used by modelling algorithms such as SVM [13]- [14]. Preprocessing can also involve text normalization and removal of irrelevant words.…”
Section: B Data Preprocessingmentioning
confidence: 99%
“…The authors suggested in [19] an approach of collecting and pre-processing real-time data from multiple e-commerce platforms, which generate user data, and gathering all personalized user data to prepare for the next data mining, and then using the data mining technology in big data to automatically recommend personalized products to satisfy the personalized needs and tastes of customers. In [20], in order to identify customer preferences, the authors proposed an improved conjoint analysis method. To evaluate their method, they compared it with other prediction algorithms namely: generalized linear model, decision tree, random forest, gradient boosted trees, and support vector machine.…”
Section: Related Workmentioning
confidence: 99%